2007
DOI: 10.1007/s11144-007-4972-0
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of benzene with propylene over MCM-36: A comparative study with MCM-22 zeolite synthesized from the same precursors

Abstract: Pillared layered MCM-36 zeolite was prepared from MCM-22 precursor with polymeric silica as pillaring agent. Both MCM-36 and MCM-22 zeolites are very active for the alkylation of benzene with propylene, and MCM-36 shows higher selectivity to cumene compared with MCM-22 zeolite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…N 2 sorption data that reflected the pore structures of samples are shown in Figure and Table . The adsorption/desorption isotherm of ERB-1 shows standard Type I isotherm, which is the characteristic isotherm of microporosity, indicating that the sample belongs to microporous materials. Moreover, compared with ERB-1, the D-ERB-1 presents a similar adsorption/desorption isotherm. The S BET and V total of D-ERB-1 shows practically almost the same value, compared with ERB-1.…”
Section: Resultsmentioning
confidence: 96%
“…N 2 sorption data that reflected the pore structures of samples are shown in Figure and Table . The adsorption/desorption isotherm of ERB-1 shows standard Type I isotherm, which is the characteristic isotherm of microporosity, indicating that the sample belongs to microporous materials. Moreover, compared with ERB-1, the D-ERB-1 presents a similar adsorption/desorption isotherm. The S BET and V total of D-ERB-1 shows practically almost the same value, compared with ERB-1.…”
Section: Resultsmentioning
confidence: 96%
“…Owing to their properties, MWW materials have been used in a number of different applications, and it has been found that they can be considered promising catalysts for several organic reactions, for example for isobutene-2-butene alkylation, 64 as well as alkylation of benzene with propylene. 65 The uniqueness of these catalysts is that they combine the properties of both conventional zeolite systems and layered materials. The expansion of the areas of application of MWW materials necessitates a deeper understanding of the impact of structural features on their activity in conversion of organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The zeolite MCM-22 is widely used in various catalytic reactions such as disproportionation of toluene [5], aromatization of methane [6], alkylation of benzene [7], alkane cracking reactions [8], methanol-to-olefin conversion [9], and also as an additive in FCC catalysts [10] due to its acidity, which is not restricted to acid sites inside the porous systems, but also presents acid sites located in the semi cavities (''cups'') on the outer surface of the crystallites [11].…”
Section: Introductionmentioning
confidence: 99%